Should the provision of home help services be contained?: Validation of the new preventive care policy in Japan - Ishibashi Tomoaki; Ikegami Naoki (BMC, 2010)
Abstract Background To maintain the sustainability of public long-term care insurance (LTCI) in Japan, a preventive care policy was introduced in 2006 that seeks to promote active improvement in functional status of elderly people who need only light care. This policy promotes the use of day care services to facilitate functional improvement, and contains the use of home help services that provide instrumental activity of daily living (IADL) support. However, the validity of this approach remains to be demonstrated. Methods Subjects comprised 241 people aged 65 years and over who had recently been certified as being eligible for the lightest eligibility level and had began using either home help or day care services between April 2007 and October 2008 in a suburban city of Tokyo. A retrospective cohort study was conducted ending October 2009 to assess changes in the LTCI eligibility level of these subjects. Cox's proportional hazards model was used to calculate the relative risk of declining in function to eligibility Level 4 among users of the respective services. Results Multivariate analysis adjusted for factors related to service use demonstrated that the risk of decline in functional status was lower for users of home help services than for users of day care services (HR = 0.55, 95% CI: 0.31-0.98). The same result was obtained when stratified by whether the subject lived with family or not. Furthermore, those who used two or more hours of home help services did not show an increase in risk of decline when compared with those who used less than two hours. Conclusions No evidence was obtained to support the effectiveness of the policy of promoting day care services and containing home help services for those requiring light care.